Guideline for Capsule Endoscopy: Obscure Gastrointestinal Bleeding - Shim, Ki-Nam; Moon, Jeong Seop; Chang, Dong Kyung; Do, Jae Hyuk; Kim, Ji Hyun; Min, Byung Hoon; Jeon, Seong Ran; Kim, Jin-Oh; Choi, Myung-Gyu (Clinical endoscopy, 2013)
Capsule endoscopy (CE) is considered as a noninvasive and reliable diagnostic tool of examining the entire small bowel. CE has been performed frequently at many medical centers in South Korea; however, there is no evidence-based CE guideline for adequate diagnostic approaches. To provide accurate information and suggest correct testing approaches for small bowel disease, the guideline on CE was developed by the Korean Gut Image Study Group, a part of the Korean Society of Gastrointestinal Endoscopy. Operation teams for developing the guideline were organized into four areas: obscure gastrointestinal bleeding, small bowel preparation, Crohn's disease, and small bowel tumor. A total of 20 key questions were selected. In preparing this guideline, MEDLINE, Cochrane library, KMbase, KISS, and KoreaMed literature searches were performed. After writing a draft of the guideline, opinions from various experts were reflected before approving the final document. The guideline should be regarded as recommendations only to gastroenterologists in providing care to their patients. These are not absolute rules and should not be construed as establishing a legal standard of care. Although further revision may be necessary as new data appear, this guideline is expected to play a role for adequate diagnostic approaches of various small bowel diseases.